Advocating sustainable building paradigm through value management - Abd-Karim, Saipol Bari; Wah, Hewwan; Jaapar, Aini; Mohamad Suhaimi, Mohamad Saifulnizam; Berawi, Mohammed Ali (University of Malaya, 2017)
Sustainability issues had become one of the top issues of Malaysia construction industry. The implication of sustainable dimensions into construction project helps in generating buildings which are energy efficient, healthy, comfortable and flexible while at the same time increases its durability. Value management (VM) is proposed as a tool used to promote sustainable building (SB). VM aims to achieve optimum value of a project based on its objectives and its approach is much similar w ith sustainability which ideally focusing on achieving values, not just economically, but environmentally and social aspects of the project. This paper investigated the practicability of the VM-SB integration in the Malaysia construction industry. It explores the development and practices of VM-SB concept as well as assessing the perfonnance criteria of integrating VM in SB projects. Findings from the questionnaire surveys which were distributed to G7 contractors show ed that the VM-SB integration is still low7 but gradually increasing. More know ledge and understanding of both concepts are needed prior to be implemented into a project as there are potentials for VM-SB concept to be adapted to all projects in the near future.